Dying for faith religiously motivated violence in the contemporary world - Al-Rasheed, Madawi; Shterin, Marat (Library of modern religion, 2009)
From India to Iraq, from London to Lahore, the relationship between religion and violence is a bitterly contested and casually misrepresented issue. This volume brings together several perspectives from a variety of fields to probe it. It seeks to shift analytical focus on to the contexts in which violence is expressed, enacted and reported.